Innovation Determinants in Morocco: A Quantitative Analysis - Houzmali, Fatima-Zahra; Krami, Rachid (International Journal of Economics and Financial Issues, 2025)
Innovation is a major economic and social development cornerstone, boosting productivity, creating jobs and strengthening the competitiveness of nations and organizations. This paper explores the determinants of innovation in Morocco through a quantitative analysis, combining a literature review and statistical analysis via Autoregressive Distributed Lag (ARDL) modeling. The results reveal that R&D expenditure (% of GDP), the number of R&D researchers and the number of patent registration have a positive and significant impact on Morocco's innovation index. a 1% increase in Morocco's GDP from R&D expenditure could boost its global innovation index (GII) by more than 19 points, while each additional 1,000 researchers per million people and each 1,000 patents registered could add 5 and 6 points respectively. These results underline the importance of R&D investment, human capital and intellectual property protection. However, variables such as public spending on education, the number of ISO-certified organizations and enrolment in higher education show no significant effect, revealing a misalignment between current policies and national needs for innovation promotion. To realize its potential, Morocco needs to adopt effective measures and national strategy, could make Morocco a major innovator at regional and international level.